2017
DOI: 10.1270/jsbbs.16115
|View full text |Cite
|
Sign up to set email alerts
|

Linkage mapping of <i>Mungbean yellow mosaic India virus</i> (MYMIV) resistance gene in soybean

Abstract: Mungbean Yellow Mosaic India Virus (MYMIV) is one of the most prevalent pathogen that limits soybean production in India. In this study RILs derived from JS335, dominant but MYMIV susceptible variety and PI171443, donor of MYMIV resistance gene in most of the MYMIV resistant varieties released in India and F2 population derived from SL525, a resistant variety released for northern India and NRC101, a susceptible genotype were used to study the inheritance of MYMIV resistance and map the gene responsible for MY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 24 publications
5
21
0
Order By: Relevance
“…Crossing is made with susceptible and resistance parents to study the inheritance of MYMV resistance. In first filial generation, the plants of all the crosses showed susceptible symptom indicating that susceptibility was dominant over resistance (Narasimhulu et al, 2016, Webster et al, 20004) Similar results on the dominant behavior of MYMV susceptibility in the F 1 were also reported in the mungbean by Khan et al (2007) and Rani et al (2017). To deduce the inheritance pattern of MYMV resistance, eight first filial crosses were forwarded to second filial generation for the study of segregating pattern.…”
Section: Resultsmentioning
confidence: 60%
“…Crossing is made with susceptible and resistance parents to study the inheritance of MYMV resistance. In first filial generation, the plants of all the crosses showed susceptible symptom indicating that susceptibility was dominant over resistance (Narasimhulu et al, 2016, Webster et al, 20004) Similar results on the dominant behavior of MYMV susceptibility in the F 1 were also reported in the mungbean by Khan et al (2007) and Rani et al (2017). To deduce the inheritance pattern of MYMV resistance, eight first filial crosses were forwarded to second filial generation for the study of segregating pattern.…”
Section: Resultsmentioning
confidence: 60%
“…Kumar et al (2015) found a region on chromosome 17 in significant linkage disequilibrium with MYMIV resistance in an association mapping study. Recently Rani et al (2017) mapped a MYMIV resistance gene on chromosome 6 very close to the two SSR markers Satt322 and GMAC7L. As viruses continuously mutate to evade resistance mechanisms of host plants, it is essential to continue to map MYMIV resistance genes from new sources to meet future challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are required to investigate whether the MYMIV resistance genes mapped in this study are related to the same gene family. The SSR markers Satt322 and GMAC7L, previously reported as linked to MYMIV resistance in G. max (Rani et al, 2017), are being successfully deployed to introgress a MYMIV resistance gene from PI 171443 into the predominant cultivated varieties of central India. However, breakdown of resistance to plant disease can frequently occur, particularly when the resistance to a specific disease is conditioned by a single gene.…”
Section: Locusmentioning
confidence: 99%
See 2 more Smart Citations